Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Inovasi terhadap Kinerja Keuangan Perusahaan - Budi Prajogo; Moh. Tahang (Neolectura, 2023)
The purpose of this study is to analyze the effect of innovative leadership, organizational culture and innovation on corporate financial performance. The research methodology used is a qualitative approach with a case study approach covering a large number of leading companies in various industries. Data was collected through in-depth interviews with company directors, managers and employees who play a role in shaping the innovation process and organizational culture. The research was conducted over a 12-month period from July 2022 to July 2023. The results showed that transformational leadership has a significant influence on the company's financial performance. A visionary leadership style that focuses on employee development and drives transformational change helps companies improve operational efficiency and competitiveness. In addition, a strong and positive corporate culture also plays an important role in improving financial performance. A culture that supports creativity, collaboration and prudent risk-taking encourages innovation and increased productivity. However, this research has some limitations, such as the limited number of companies included in the case studies and its focus on qualitative data. The research highlights the importance of adopting innovative leadership and building a culture that supports innovation as strategic steps for organizations to improve their financial performance